Social supports moderate the effects of child adversity on neural correlates of threat processing. (April 2020) - Wymbs, Nicholas F.; Orr, Catherine; Albaugh, Matthew D.; Althoff, Robert R.; O'Loughlin, Kerry; Holbrook, Hannah; Garavan, Hugh; Montalvo-Ortiz, Janitza L.; Mostofsky, Stewart; Hudziak, James; Kaufman, Joan
Abstract: Background: Child abuse and other forms of adversity are associated with alterations in threat processing and emotion regulation brain circuits. Objective: The goal of the current investigation is to determine if the availability of positive social support can ameliorate the negative impact of adversity on these brain systems. Participants and setting: Subjects included 55 children ages 7–16 (X = 11.8, SD = 2.0). Approximately one-third of the cohort had no significant history of adversity, one-third had a history of moderate adversity, and one-third had a history of severe adversity. Brain imaging was conducted at the University of Vermont using a 3.0 T Philips scanner. Methods: The Emotional Go-NoGo task with fearful and calm facial stimuli was used to assess the neural correlates of threat processing and emotion regulation in children during functional magnetic resonance imaging (fMRI). Dimensional measures of anxiety, social supports, and children's adverse experiences were also obtained. Results: A conjunction analysis was used to test if trauma-related brain activation in responding to fearful vs. calm targets was impacted by social support. This approach identified multiple activation foci, including a cluster extending from the left amygdala to several other key brain regions involved in emotion regulation, including the orbitofrontal cortex, anterior cingulate cortex (ACC), anterior insula, nucleus accumbens, and frontal pole (Family Wise Error (FWE) correction, p < 0.05). Conclusions: Greater social support may reduce the effect that adversity has on neural processing of threat stimuli, consistent with the protective role of positive supports in promoting resilience and recovery demonstrated in the literature.